2008
DOI: 10.1017/s1047951108002138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diastolic ventricular function in fetuses of diabetic mothers using tissue Doppler

Abstract: Pulsed tissue Doppler, when used in fetuses of diabetic mothers and compared with fetuses of nondiabetic mothers, shows evidence of impaired diastolic function, independently of the presence of myocardial hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
63
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 36 publications
13
63
1
Order By: Relevance
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 86%
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 86%
“…96,300 In a prospective study in 25 growth restricted fetuses, TDI demonstrated both systolic and diastolic tissue velocity abnormalities compared with normal fetuses, whereas pulsed Doppler detected only an increase in left ventricular MPI with all other indexes, including E/A ratios, outflow tract velocities, and right ventricular MPI, being similar to those in controls. 301 TDI has also been applied to the assessment of diastolic dysfunction in fetuses of diabetic mothers and other complicated pregnancies 302,303 and in the presence of TTTS, 304 CHD, 305 heart failure, 306 and arrhythmias. 307 In summary, TDI evaluation of fetal cardiac function may be considered in clinical practice, although its usefulness has not been established and the technique currently remains a research tool.…”
Section: Tissue Doppler Imagingmentioning
confidence: 99%
“…Fetal cardiac dysfunction may be due to an intrinsic myocardial disease or to a secondary adaptive mechanism. The latter is particularly important because the heart seems to be a central organ in the fetal adaptive response to a variety of insults [5,6,7,8]. Consequently, assessment of fetal cardiac function may be helpful in the diagnosis or monitoring of several fetal conditions [4,5,6,7,8].…”
Section: Importance Of Fetal Cardiac Functionmentioning
confidence: 99%